Analisis Perbandingan Bahasa Pemrograman Untuk Menentukan Keprimaan Bilangan Menggunakan Teorema Fermat - Ofelius Laia (Universitas Methodist Indonesia, 2024)
This study aims to compare the performance of several programming languages, namely PHP, Java, and Python, in determining the primality of numbers using Fermat's Theorem. The selection of programming languages is based on their popularity and efficiency in cryptographic algorithm implementation. The method used is a comparative experiment, with measurement parameters including execution time, memory consumption, and result accuracy. The results show that Java excels in execution efficiency with the fastest time, while PHP demonstrates the lowest memory consumption. Although Python is slower, all three programming languages produced accurate results in primality testing. This research concludes that Java is the best choice for applications requiring high speed, while PHP is more suitable for resource-limited applications. Future research is recommended to test more programming languages and use a larger number dataset.